2019
DOI: 10.1051/0004-6361/201935374
|View full text |Cite
|
Sign up to set email alerts
|

Superflares on AB Doradus observed with TESS

Abstract: We present short-cadence data of the ultra-active star AB Dor measured by the Transiting Exoplanet Survey Satellite (TESS). In the TESS light curves of AB Dor, we found numerous flare events in addition to time-variable rotational modulation with an amplitude of up to 7%. We identified eight superflares (releasing more than 1034 erg) and studied their morphologies and energetics. We compared these flares to both the most energetic solar flare seen in total solar irradiance measurements as well as to a very ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…Extensive X-ray studies of AB Dor have been presented, for example, by Kuerster et al (1997), who discuss the ROSAT data on AB Dor, and by Lalitha et al (2013), who present simultaneous XMM-Newton and VLT observations of AB Dor which, in particular, cover a very large flare. This flare was also studied by Schmitt et al (2019), who show the superflare nature of such flares observed by TESS during the first two months of data taking. Thus, in summary, according to our current understanding, AB Dor is rather nearby (d = 15.3 pc), ultra-active, and a pre-main-sequence object with a radius of 0.96 ± 0.06 R (see Guirado et al 2011), which shows strong signatures of magnetic activity at all wavelengths.…”
Section: Ab Doradusmentioning
confidence: 84%
See 1 more Smart Citation
“…Extensive X-ray studies of AB Dor have been presented, for example, by Kuerster et al (1997), who discuss the ROSAT data on AB Dor, and by Lalitha et al (2013), who present simultaneous XMM-Newton and VLT observations of AB Dor which, in particular, cover a very large flare. This flare was also studied by Schmitt et al (2019), who show the superflare nature of such flares observed by TESS during the first two months of data taking. Thus, in summary, according to our current understanding, AB Dor is rather nearby (d = 15.3 pc), ultra-active, and a pre-main-sequence object with a radius of 0.96 ± 0.06 R (see Guirado et al 2011), which shows strong signatures of magnetic activity at all wavelengths.…”
Section: Ab Doradusmentioning
confidence: 84%
“…For the construction of the time-brightness plot, we split the light curve in chunks of length equal to the period derived by Schmitt et al (2019), that is, 0.514275 days. Assuming that this signal's period is indeed the star's rotation period, each of these chunks then represents one rotation of AB Dor.…”
Section: Light Curvementioning
confidence: 99%
“…With its colour of BP-RP = 2.98, it is quite similar to the stars considered here. Schmitt et al (2019) analysed TESS and XMM-Newton flare observations of the young active star AB Dor (spectral type K0) and demonstrated that the optical output of these flares is likely of the order of the X-ray output and possibly higher by up to one order of magnitude. In this context, we note that the total energy output of our most extreme X-ray event (from ID 95) coincides nicely with that obtained for Gaia EDR3 5495481200071568640 in the optical.…”
Section: Stellar Flare Eventsmentioning
confidence: 99%
“…A great number of flaring events are known to occur in AB Dor A (see Schmitt et al 2019, and references therein). From these and previous studies, it has been well-established that the corona of this star presents evidence for both compact and extended structures.…”
Section: Flaring Loops Hypothesismentioning
confidence: 99%
“…It is a multiple system formed by two pairs of stars separated by 9 , AB Dor A/C and AB Dor Ba/Bb (Close et al 2005;Guirado et al 2006), which have lent their names to the AB Dor moving group (AB Dor-MG). The main star of this system, the K0 dwarf AB Dor A, is a fast rotator (period of 0.5 days; see Table 1), which presents strong emission at all wavelengths, from radio to X-rays (see Schmitt et al 2019, and references therein). It has been well studied by the HIPPARCOS satellite (Lestrade et al 1995;Lindegren & Kovalevsky 1995) and VLBI arrays (Lestrade et al 1995;Guirado et al 1997).…”
Section: Introductionmentioning
confidence: 99%